Use of Factory-Waste Shingles and Cement Kiln Dust to Enhance the Performance of Soil Used in Road Works. (8th February 2010) - Ahmed, Aly; Shehata, Medhat; Easa, Said
Abstract : An experimental work was conducted to study the use of factory-waste roof shingles to enhance the properties of fine-grained soil used in road works. Cement kiln dust (CKD), a cogenerated product of Portland cement manufacturing, was used as a stabilizing agent while the processed shingles were added to enhance the soil tensile strength. The effects of shingles on strength and stability were evaluated using the unconfined compressive strength, splitting tensile strength, and California Bearing Ratio (CBR) tests. The results showed that the use of CKD alone resulted in a considerable increase in the unconfined compressive strength but had a small effect on the tensile strength. The addition of shingles substantially improved the tensile strength of the stabilized soil. A significant reduction in the capillary rise and a slight decrease in the permeability were obtained as a result of shingle addition. An optimal shingle content of 10% is recommended to stabilize the soil.